Price Changes - Stickiness and Internal Coordination in Multiproduct Firms - Wilko Letterie; Øivind Anti Nilsen (Center for Economic Studies and ifo Institute (CESifo), 2016)
We assess empirically the micro-foundations of producers' sticky pricing behaviour. The intertemporal profit function considered accounts for various functional forms of menu costs. The focus is on the analysis of multiproduct plants, and the menu costs therefore also allow for economies of scope. The structural model developed is tested on a merged panel of monthly product- and plant-specific producer prices and yearly plant-specific producer statistics for Norwegian plants. We find evidence of linear and fixed menu costs that account for inaction of price adjustment. Convex menu costs are statistically significant but of moderate importance. Finally, our estimates suggest economies of scope in adjusting prices resulting in (incomplete) synchronization of price changes.
Keywords: E30; E31; 330; price setting; micro data; multiproduct firms